The effects of Thymus capitatus essential oil topical application on milk quality: a systems biology approach - Ralph Nehme; Chiara Gini; Elise Vanbergue; Sergine Even; Filippo Biscarini; Sonia Andrés; Lucie Rault; Faustine Noel; Valerie Hardit; Said Bouhallab; David M. Pereira; Riadh Ksouri; et al. (Scientific Reports)
Abstract Essential oils (EO) are known for their antibacterial and anti-inflammatory properties and can be used as an alternative to reduce the reliance on antimicrobials in dairy cattle. While many studies have explored the beneficial properties of EO in vitro, their effects on milk quality and milk microbiota, when applied directly to the udder skin, remain relatively unknown. This study aimed to investigate the impact of Thymus capitatus essential oil (TCEO), known for its high antibacterial and antioxidant properties, on milk microbiota using 16S rRNA sequencing, the lipidomic profile via liquid chromatography-quadrupole time-of-flight mass spectrometry, udder skin microbiota, and inflammatory biomarkers of dairy cows at the end of lactation. Sixteen-quarters of 12 Holstein cows were selected, and TCEO was topically applied to the udder skin twice a day for 7 days. Milk was collected aseptically on days 0, 7, 21, and 28 before morning farm milking. The results showed no significant changes in microbiota composition after the EO treatment in alpha and beta diversity or taxonomical composition at the phylum and genus levels. TCEO induced limited changes in the milk lipidome, primarily affecting diacylglycerols at T21. The treatment did not affect inflammatory biomarkers, milk sensory properties, or quality. Our study is the first to demonstrate that a local application of 10% TCEO on cow’s quarters does not significantly alter milk quality or microbiota composition in milk and skin. More studies should be conducted to ensure the safe use of TCEO in dairy cows and explore its potential benefits on antibiotic-resistant bacteria as an alternative or support for antibiotic therapy.